2019
DOI: 10.1111/coep.12454
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven Drafting: Applying Econometrics to Employ Quarterbacks

Abstract: We show that firms can employ data‐driven methods to improve their hiring decisions. Specifically, we use data available to National Football League (NFL) teams prior to the NFL draft to estimate econometric models that predict the future performance of drafted quarterbacks. As our methods are replicable, stakeholders can use them to improve the draft's efficiency and help it accomplish its mission to promote competitive balance. Furthermore, data‐driven methods such as ours can help firms avoid biases against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Section 3.1 revealed that good passing ability is effectively a prerequisite for NFL selection, so this outcome confirms the results in our preliminary analysis that a key indicator of the NFL performance of good college passers is their rushing ability. The finding that passing ability is not a significant determinant of the NFL performance of selected quarterbacks is consistent with the conclusions of Wolfson et al (2011) and Pitts and Evans (2018), and the result that college rushing ability is positively correlated with NFL success concurs with Rosen and Olbrecht (2020). Katz and Bradshaw (2015) postulate that good college rushers succeed in the NFL because good runners have the ability to extend drives.…”
Section: Nfl Performancesupporting
confidence: 73%
See 3 more Smart Citations
“…Section 3.1 revealed that good passing ability is effectively a prerequisite for NFL selection, so this outcome confirms the results in our preliminary analysis that a key indicator of the NFL performance of good college passers is their rushing ability. The finding that passing ability is not a significant determinant of the NFL performance of selected quarterbacks is consistent with the conclusions of Wolfson et al (2011) and Pitts and Evans (2018), and the result that college rushing ability is positively correlated with NFL success concurs with Rosen and Olbrecht (2020). Katz and Bradshaw (2015) postulate that good college rushers succeed in the NFL because good runners have the ability to extend drives.…”
Section: Nfl Performancesupporting
confidence: 73%
“…Pitts and Evans (2018) show that quarterback Wonderlic scores -a test of cognitive ability -are positively correlated with NFL performance. Rosen and Olbrecht (2020) find that quarterbacks who demonstrated 'functional mobility' in college performed better than those who did not. The authors measure function mobility using rushing yards per attempt (positively correlated with NFL performance) and the log of the runpassing completion ratio (negatively correlated with NFL performance).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Nearly all previous studies that examined NFL quarterback performance attempted to project performance using only variables known to teams before quarterbacks were drafted (e.g., see Berri & Simmons, 2011; Cook et al, 2020; Craig & Winchester, 2021; Hendricks et al, 2003; Kitchens, 2015; Kuzmits & Adams, 2008; Mirabile, 2005; Pitts & Evans, 2018; Rosen & Olbrecht, 2020; and Wolfson et al, 2011). Thus, these studies were primarily interested in how NFL teams could identify talented players in the draft.…”
Section: Data and Empirical Methodsmentioning
confidence: 99%